Efficacy and safety of magnesium isoglycyrrhizinate injection in patients with acute drug‐induced liver injury: A phase II trial. (21st August 2019) - Wang, Yongfeng; Wang, Zhenghua; Gao, Mengqiu; Zhong, Haijun; Chen, Chengwei; Yao, Yang; Zhang, Zhongshun; Zhang, Xia; Li, Fujian; Zhang, Jianzhong; Gu, Hong‐Mei; Chen, Yingxuan; et al.
Abstract: Background: Drug‐induced liver injury (DILI) is the most common reason for a drug to be withdrawn from the market. Apart from stopping the offending drug, no regimens are available for treating idiosyncratic DILI in clinical practice. Methods: We carried out a randomized, double‐blind, multidoses, active drug controlled, multicentre phase II trial to assess the safety and efficacy of the study drug, magnesium isoglycyrrhizinate (MgIG), as compared to tiopronin, a standard therapy for DILI in China. The primary outcome was the proportion of alanine aminotransferase (ALT) normalization at week 4 after study drug administration. Logistic regression was used to examine the odds of ALT normalization between low dose (Group A) and high dose (Group B) vs active control (Group C). Results: One hundred and seventy‐four eligible subjects were randomized and enrolled into three groups: 59 in group A, 56 in group B and 59 in group C. It was shown that group A and group B lowered ALT level even at early stage of study drug administration; when compared with Group C (61.02%), the proportions of ALT normalization at week 4 were significantly greater in Group A (84.75%, P = .0029) and Group B (85.71%, P = .0037) respectively. The results from the univariate logistic model showed that the odds of ALT normalized among subjects in Group A were about 3.6 times greater (OR = 3.55, 95% CI: 1.47‐8.57, P = .0049) than subjects in Group C. Similar effect was observed among subjects in Group B (OR = 3.83, 95% CI: 1.54‐9.55, P = .0039). Conclusions: This trial provided preliminary evidence that MgIG is an effective and safe treatment for patients with acute DILI.